PHYSICAL-CHEMICAL CHARACTERIZATION OF THE SEDIMENTS OF THE WETLAND LAGUNA BELLA IN THE JUNGLE OF HUÁNUCO, PERU - Zavaleta De la Cruz, Lauriano (2021)
The lagoons in the Amazon are being impacted by agricultural activities and the information about their sediments is scarce; therefore, the objective of the study was to determine the physicochemical characteristics of the sediments of the Laguna Bella, wetland which will contribute to the knowledge of its environmental quality. Thus, using standardized techniques, sediments collected at six sampling points were analyzed. The results show the values of density, organic matter, conductivity, pH, organic matter, N, P, Pb, Cu, Fe, Mn, Zn and K, which were compared with five international standards. Considering the Ontario standard, organic matter is below the severe effect level; N is between the lowest and most severe effect level, while P is below the lowest effect level concentration; Pb is at a moderately contaminated level, according to the USEPA standard, but exceeds the NOAA standard. Cu exceeded the maximum permissible level of the NOAA standard; Fe exceeds the maximum permissible level of USEPA, Ontario, and NOAA standards; Mn exceeds the maximum allowable level of NOAA standards, and Zn exceeds the NOAA standard. It is concluded that the density of the sediments is uniform, the pH is slightly alkaline, the salinity is negligible, and the concentration of metals, such as Fe > Mn > Zn > Pb > Cu, exceeds international standards and indicates the deterioration of the environmental quality of the wetland.